Biallelic variants in CTU2 cause DREAM‐PL syndrome and impair thiolation of tRNA wobble U34. Issue 11 (29th July 2019) - Shaheen, Ranad; Mark, Paul; Prevost, Christopher T.; AlKindi, Adila; Alhag, Ahmad; Estwani, Fatima; Al‐Sheddi, Tarfa; Alobeid, Eman; Alenazi, Mona M.; Ewida, Nour; Ibrahim, Niema; Hashem, Mais; et al.
Abstract: The wobble position in the anticodon loop of transfer ribonucleic acid (tRNA) is subject to numerous posttranscriptional modifications. In particular, thiolation of the wobble uridine has been shown to play an important role in codon‐anticodon interactions. This modification is catalyzed by a highly conserved CTU1/CTU2 complex, disruption of which has been shown to cause abnormal phenotypes in yeast, worms, and plants. We have previously suggested that a single founder splicing variant in human CTU2 causes a novel multiple congenital anomalies syndrome consisting of dysmorphic facies, renal agenesis, ambiguous genitalia, microcephaly, polydactyly, and lissencephaly (DREAM‐PL). In this study, we describe five new patients with DREAM‐PL phenotype and whose molecular analysis expands the allelic heterogeneity of the syndrome to five different alleles; four of which predict protein truncation. Functional characterization using patient‐derived cells for each of these alleles, as well as the original founder allele; revealed a specific impairment of wobble uridine thiolation in all known thiol‐containing tRNAs. Our data establish a recognizable CTU2 ‐linked autosomal recessive syndrome in humans characterized by defective thiolation of the wobble uridine. The potential deleterious consequences for the translational efficiency and fidelity during development as a mechanism for pathogenicity represent an attractive target of future investigations.